Détermination des profils de sensibilité des souches de P. aeruginosa d’origine pathologique et recherche de l’effet post-antibiotique - ARIBI AMEL (My University, 2012)
P. aeruginosa always been considered a difficult target for chemotherapy against infection. When the isolated bacteriumis found responsible for the infection, the choice of antibiotic is guided by the study of its sensitivity in vitro. While some bacterial resistance to express little or not in vitro. This is why we tried to look for the reliability of the results of determining the sensitivity profiles of the strains in vitro by the diffusion method on agar medium (antibiogram), by looking for the minimum inhibitory concentrations and the minimum bactericidal concentrations. We also looked for the existence of a post-antibiotic effect of the antibiotics which appear to be the most effective. The results show that among the antibiotics tested only aminoglycosides (AN, CN) have has a bactericidal effect with an MIC included in the range of critical sensitivity values. Aminoglycosides can also exert a post-antibiotic effect even at low concentrations and after a short period of contact with the multi-resistant strain tested. On the other hand, β-lactams (IPM, CRO and CTX) exert bacteriostatic activities, and a post-antibiotic effect depends on the contact time between the bacteria and the antibiotic. ---------------------------------------------------------------------------------------- P. aeruginosa الزنجارية تعتبر دائمًا هدفًا صعبًا في العلاج الكيميائي المضاد للعدوى. عندما تم العثور على البكتيريا المعزولة المسؤولة عن العدوى،و يتم اختيار المضاد الحيوي من خلال دراسة حساسيتها في المختبر. في حين ان بعض البكتيرياالمقاومة للتعبير ضئيلة أو معدومة في المختبر. ولهذا السبب حاولنا البحث عن موثوقية نتائج تحديد ملامح الحساسية للسلالات في المختبر بطريقة الانتشار على وسط أجار (المضاد الحيوي)، من خلال البحث عن الحد الأدنى من التركيزات المثبطة والحد الأدنى من تركيزات مبيد الجراثيم. كما بحثنا أيضًا عن وجود تأثير ما بعد المضاد الحيوي للمضادات الحيوية التي يبدو أنها الأكثر فعالية. وتظهر النتائج أنه من بين المضادات الحيوية التي تم اختبارها فقط أمينوغليكوزيدات (AN، CN) لديها له تأثير مبيد للجراثيم مع MIC مدرج في نطاق قيم الحساسية الحرجة. أمينوغليكوزيدات يمكن كما أن له تأثيرًا ما بعد المضاد الحيوي حتى عند التركيزات المنخفضة وبعد فترة قصيرة من التلامس مع السلالة المتعددة المقاومة التي تم اختبارها. من ناحية أخرى، تمارس β-lactams (IPM وCRO وCTX) أنشطة مثبطة للجراثيم، ويعتمد تأثير ما بعد المضاد الحيوي على وقت الاتصال بين البكتيريا والمضاد الحيوي. ---------------------------------------------------------------------------------------------- P. aeruginosa toujours été considéré comme une cible difficile en chimiothérapie anti-infectieuse. Lorsque la bactérie isolée est jugée responsable de l'infection, le choix de l'antibiotique est guidé par l'étude de sa sensibilité in vitro. Alors que certaines résistances bactériennes s'expriment peu ou pas in vitro. Raison pour la quelle on a essayé de chercher la fiabilité des résultats de détermination des profils de sensibilité des souches in vitro par la méthode de diffusion sur milieu gélosé (antibiogramme), en cherchant les concentrations minimales inhibitrice et les concentrations minimales bactéricides. Aussi on a recherché l’existence d’un effet post-antibiotiques des antibiotiques qui se montrent les plus efficaces. Les résultats montrent que parmi les antibiotiques testées les aminosides (AN, CN) seulement ont a un effet bactéricide avec une CMI inclue dans la gamme des valeurs critiques de sensibilité. Les aminosides peuvent exercer aussi un effet post- antibiotique même à des faibles concentrations et après de courte durée de mise en contacte avec la souche multirésistante testée. Par contre les β- lactamines (IPM, CRO et CTX) exercent une activitées bactériostatiques, et un effet post antibiotique dépend de temps de contact entre la bactérie et l’antibiotique. Mots clés : P. aeruginosa, Antimicrobiens, résistance, bactériostatique CMI, bactéricide (CMB), effet post- antibiotique. P. aeruginosa always been considered a difficult target for chemotherapy against infection. When the isolated bacteriumis found responsible for the infection, the choice of antibiotic is guided by the study of its sensitivity in vitro. While some bacterial resistance to express little or not in vitro. This is why we tried to look for the reliability of the results of determining the sensitivity profiles of the strains in vitro by the diffusion method on agar medium (antibiogram), by looking for the minimum inhibitory concentrations and the minimum bactericidal concentrations. We also looked for the existence of a post-antibiotic effect of the antibiotics which appear to be the most effective. The results show that among the antibiotics tested only aminoglycosides (AN, CN) have has a bactericidal effect with an MIC included in the range of critical sensitivity values. Aminoglycosides can also exert a post-antibiotic effect even at low concentrations and after a short period of contact with the multi-resistant strain tested. On the other hand, β-lactams (IPM, CRO and CTX) exert bacteriostatic activities, and a post-antibiotic effect depends on the contact time between the bacteria and the antibiotic.